Stress and psychological well-being: study in parents of children with special needs - Veiga-Branco, Augusta (2017)
Existing research, mainly conducted with mothers, shows that families parenting a child special needs experience higher levels of emotional distress compared to families with children with a typical development (Delambo, et al, 2011; Lecavalier, et al, 2006, Lee, 2013). This is the first empirical research (to our knowledge) that will be conducted involving both parents of a child with special needs from the northern and interior region of Portugal. This quantitative, descriptive and cross-sectional research as the following aims: (i) to analyze the associations between parental stress and parents’ psychological well-being; (ii) to evaluate the influence of individual variables on parents’ psychological wellbeing. Data consisted of parents´ responses on the Portuguese version of the Parental Stress Scale (Mixão, Leal & Maroco, 2007) and Satisfaction with Life Scale (Simões, 1992). The survey will be conducted between the 15th of January and the 15th of March of 2017. Starting from the acquired consciousness about the fact the stress faced by families raising children SN may continue during adolescence and adult life, influencing the quality of family relationships on a long term, results will be presented. In fact, the relevance of the data obtained with families parenting children with special needs will be discussed considering the need of promoting the optimal development of parents with a child with special needs, in a short and long term in time.